The Relationship Between Instagram Use and the Likelihood of Female University Students Experiencing Cyber Harassment - Sandra Clarissa Umbu Datta; Roky Konstantin Ara (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Instagram is one of the most widely used social media platforms among female university students. While the platform enables self-expression, social interaction, and information sharing, it simultaneously increases users’ exposure to cyber harassment, particularly against women. This study examines the relationship between Instagram use and the likelihood of female university students experiencing cyber harassment. Guided by Computer-Mediated Communication (CMC) theory, this research employs a quantitative approach. Data were collected through an online questionnaire distributed to 200 female students from two universities in the Special Region of Yogyakarta—Universitas Islam Indonesia (UII) and Universitas Gadjah Mada (UGM). The Spearman Rank correlation test was used to assess the strength of the relationship between Instagram use and cyber harassment, while the Mann–Whitney test examined differences between institutional groups. The findings reveal a very strong positive correlation between Instagram use and the likelihood of experiencing cyber harassment (Rs > 0.90). The Mann–Whitney test indicates a statistically significant difference between groups (p = 0.016); however, the small effect size suggests that institutional affiliation does not substantially mitigate the risk of cyber harassment. Instead, vulnerability is primarily shaped by usage patterns, exposure, and online behavior. These findings demonstrate that cyber harassment is a systemic issue affecting female university students regardless of institutional context. The study highlights the urgent need for digital literacy education, gender-sensitive university policies, and stronger institutional and platform-level interventions to protect women in online spaces.